The Effect of Industrial Work Practices, Learning Achievement, and Self-Efficiency on Vocational High School Students' Job Readiness - Asmawan, Moh. Chairil; Pertiwi, Herlina Yuliana; Mustofa, Rochman Hadi (Universitas Muhammadiyah Surakarta, 2022)
Vocational high schools are always required to prepare graduates to become ready-to-work graduates in the business and industrial world. Moreover, student job readiness is influenced by internal and external factors. For this reason, this study aims to examine 1) the effect of industrial work practices on vocational high school students' job readiness, 2) the influence of learning achievement on vocational high school students' job readiness, 3) the effect of self-efficacy on vocational high school students job readiness, 4) the influence of industrial work practices, achievement learning, and self-efficacy simultaneously on the vocational high school students' job readiness. This quantitative study used a survey method involving 78 samples of respondents, while the research location was at SMK Negeri 6 Surakarta. The data collection technique employed a questionnaire, while the data analysis utilized multiple linear regression analysis. The study results revealed: 1) Industrial work practices had a significant effect on job readiness; 2) Learning achievement had a significant effect on job readiness; 3) Self-efficacy had a significant effect on job readiness; 4) Industrial work practices, learning achievement, and self-efficacy simultaneously had a significant effect on job readiness. It proves that job readiness can be influenced by industrial work practices, learning achievement, and self-efficacy